On the Convergence of a Nonlinear Boundary-Value Problem in a Perforated Domain - Yulia Koroleva (International Journal of Differential Equations)
We consider a family with respect to a small parameter of nonlinear boundary-value problems as well as the corresponding spectral problems in a domain perforated periodically along a part of the boundary. We prove the convergence of solution of the original problems to the solution of the respective homogenized problem in this domain.